Amiodarone and risk of liver cirrhosis: a nationwide, population-based study - Huang CH; Lai YY; Kuo YJ; Yang SC; Chang YJ; Chang KK; Chen WK (Dove Medical Press, 2019)
Ching-Hui Huang,1–3,* Ya-Yun Lai,4,* Yu-Jui Kuo,4,5 Su-Ching Yang,6 Yu-Jun Chang,7 Kuo-Kuan Chang,8 Wen-Kang Chen4 1Division of Cardiology, Department of Internal Medicine, Changhua Christian Hospital, Changhua, Taiwan; 2Department of Beauty Science, Graduate Institute of Beauty Science Technology, Chienkuo Technology University, Changhua, Taiwan; 3School of Medicine, College of Medicine, Kaohsiung Medical University, Kaohsiung, Taiwan; 4Department of Applied Cosmetology, National Tainan Junior College of Nursing, Tainan, Taiwan; 5Department of Traditional Chinese Medicine, Tainan Municipal Hospital (Managed by Show Chwan Medical Care Corporation), Tainan, Taiwan; 6Department of Nursing, National Tainan Junior College of Nursing, Tainan, Taiwan; 7Epidemiology and Biostatistics Center, Changhua Christian Hospital, Changhua, Taiwan; 8Department of Hepatogastroenterology, Tainan Municipal Hospital (Managed by Show Chwan Medical Care Corporation), Tainan, Taiwan *These authors contributed equally to this work Background: Liver cirrhosis is an uncommon but not rare side effect of amiodarone-induced hepatotoxicity. Patients with hepatitis B virus and hepatitis C virus infections are at a high risk for developing liver cirrhosis. However, the relationship between this treatment and risk of liver cirrhosis in high-risk chronic hepatitis B and chronic hepatitis C patients is unknown.Patients and methods: The present study identified amiodarone users (N=8,081) from the Taiwan National Health Insurance Research Database from 1997 through 2013. A total of 32,324 subjects with age, comorbidities, gender, and index date-matched non-amiodarone users were selected as controls (non-amiodarone cohort). The incidences of cumulative liver cirrhosis were compared between cohorts. Stratified Cox’s regression hazard models were used to assess possible comorbidity-attributable risks for liver cirrhosis.Results: The amiodarone cohort had a nonsignificant risk of liver cirrhosis compared with the non-amiodarone cohort, with a HR of 1.17 (95% CI: 0.93–1.47; P=0.1723). Patients with specific comorbid diseases, including type 2 diabetes mellitus, chronic hepatitis B, chronic hepatitis C, and heart failure, were probably at a high risk of developing liver cirrhosis. The use of statins was associated with a significant 42% reduction in the risk of liver cirrhosis.Conclusion: Patients in the amiodarone cohort had no excess risk of liver cirrhosis compared with patients in the non-amiodarone cohort. Long-term surveillance for liver toxicity in high-risk patients with amiodarone treatment is suggested. Keywords: amiodarone, liver cirrhosis, Taiwan, hepatitis